(untitled) (Lex localis - Journal of Local Self-Government, 2025)
This comparative analysis explores the challenges faced by key workers in the health systems of the United Kingdom and Saudi Arabia, highlighting workforce dynamics, policy frameworks, and healthcare infrastructure. The study examines common issues such as staffing shortages, burnout, and digital transformation, while contrasting the UK’s publicly funded NHS with Saudi Arabia’s privatization efforts under Vision 2030. Findings reveal that while both countries struggle with retention and recruitment, Saudi Arabia relies more on expatriate labour, whereas the UK faces significant budget constraints and recruitment shortages in the aftermath of the UK leaving the European Union. The research underscores the need for strategic workforce policies, enhanced healthcare financing, and improved digital health solutions to address these systemic challenges in both nations.